Effect of the molecular structure of the host materials on the lifetime of green thermally activated delayed fluorescent organic light-emitting diodes1. Issue 31 (21st August 2015) - Im, Yirang; Song, Wook; Lee, Jun Yeob
<x xml:space="preserve">Abstract</x> The effect of the molecular structure of the host materials on the efficiency and lifetime of the green thermally activated delayed fluorescent devices was studied using two dibenzothiophene derived host materials.